Sprachhandlung Einladung/Vorschlag/Verabredung im Deutschen und Polnischen - Prokop, Izabela (Wydawnictwo Naukowe UAM, 1989)
The article contains a definition of the act of invitation against the background of classification of speech acts, and then the survey of linguistic structures used in this type of situation together with the pragmatic analysis of the latter. The replies (replicas) used together with "invitation" formulas were also included in the analysis. The result of the study is an observation of a high degree of convergence of these utterances in German and Polish.